What motivates employees to use social media at work? A perspective of self-determination theory. Issue 1 (24th September 2021) - Wei, Shaobo; Chen, Xiayu; Liu, Chunli
Abstract : Purpose: The authors develop a conceptual model to examine how three basic psychological needs (i.e. needs for competence, autonomy and relatedness) affect employee social media use (i.e. work- and social-related use). The authors propose that the need for autonomy positively moderates the relationship between need for competence and work-related use, whereas it negatively moderates that between need for relatedness and social-related use. Design/methodology/approach: To test the proposed model, 332 internal and 271 external social media users in the workplace were recruited. Findings: The results indicate that needs for competence and autonomy and needs for relatedness and autonomy positively affect the work- and social-related use, respectively, of internal and external social media. Need for autonomy positively moderates the relationship between need for competence and work-related use of internal social media, and it negatively moderates that between need for relatedness and the social-related use of internal social media. Need for autonomy has no moderating effect on the relationship between need for competence and work-related use, whereas it negatively moderates the relationship between need for relatedness and the social-related use of external social media. Originality/value: First, the authors' findings offer significant empirical support for the different social media uses, namely work and social related. Second, this study highlights the importance of psychological needs of employees in determining the form of social media use. Third, this study empirically demonstrates the differences in psychological needs and social media use between two different social media contexts.